Experiences of people with HIV/AIDS (PLWHA) at the critical condition due to AIDS - Sukarja, I Made; Sutedja, Endang; Nursiswati, .; Sukawana, I Wayan; Sundayana, I Made (International Journal of Research in Medical Sciences, 2017)
Background: PLWHA who suffered critical condition and being treated in intensive care the majority (84%) due to Pneumocystis carinii pneumonia, 47% experienced respiratory failure, sepsis, 12% and 11% neurologic disease. The death rate PLHIV patients treated in intensive reaches 83%. Of all patients passing through a critical phase, 27% survived for 1 year, 18% survive the second year, 13% survived 3 years and 11% last more than four years. They have the experience that need to be explored in a comprehensive manner to provide support to people living with HIV else. Methods: This research was conducted through qualitative research with phenomenological approach that focuses on the depth of the process through in-depth interviews on 10 participants. Participants in this study were HIV-positive people who visit the Polyclinic Teratai Hasan Sadikin Hospital in Bandung. Recruitment of participants was done by purposive sampling with criteria for inclusion namely 1) PLHIV been treated in hospital with critical conditions, 2) Ability to communicate with tray, 3) People who say they remember past experiences related to the care in critical condition. Results: The data were analysed to identify themes about the experiences of people living with HIV during critical condition. The results found six themes namely: 1) experiencing emotional response, 2) striving to overcome the feelings and the impact of illness, 3) closer to God, 4) undergoing their destiny as People Living with HIV/AIDS (PLWHA), 5) received support and prayers of people around, and 6) has a hope of a cure. Conclusions: PLWHA treated in a critical condition experience threat of death from opportunistic infections and had the psychological burden of disease due to the stigma of HIV/AIDS. This makes them slumped physically and psychologically, thus they felt helpless. The recommendation from the results of this research is that communities, families and health workers should provide a support system to people living with HIV in order to increase life expectancy due to a collapsed condition and hopelessness.